2007
DOI: 10.1037/1089-2680.11.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Lessons from Environmental Psychology: The Case of Biophilic Architecture

Abstract: A review of findings from the field of environmental psychology shows that humans are aesthetically attracted to natural contents and to particular landscape configurations. These features are also found to have positive effects on human functioning and can reduce stress. However, opportunities for contact with these elements are reduced in modern urban life. It is argued how this evolution can have subtle but nontrivial adverse effects on psychological and physiological well-being. These can be countered by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
208
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 251 publications
(231 citation statements)
references
References 72 publications
6
208
0
17
Order By: Relevance
“…Today, many people spend upwards of 90% of their lives in buildings (Evans & McCoy, 1998). Studies indicate that aesthetic qualities of architecture have an impact on our mood, cognitive functioning, behavior, and even mental health (Adams, 2014;Hartig, 2008;Joye, 2007). This evidence coincides with a flourish of interest in the intersection of neuroscience and architecture (Dance, 2017;Robinson & Pallasmaa, 2015;Mallgrave, 2010;Eberhard, 2008).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Today, many people spend upwards of 90% of their lives in buildings (Evans & McCoy, 1998). Studies indicate that aesthetic qualities of architecture have an impact on our mood, cognitive functioning, behavior, and even mental health (Adams, 2014;Hartig, 2008;Joye, 2007). This evidence coincides with a flourish of interest in the intersection of neuroscience and architecture (Dance, 2017;Robinson & Pallasmaa, 2015;Mallgrave, 2010;Eberhard, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…According to habitat theory, humans evolved to prefer landscapes containing visual features and spatial configurations that favor survival (Appleton, 1975). People may have an innate visual preference for moderately complex, savannah-like environments ( Joye, 2007;Balling & Falk, 1982), because these areas signal both safety and nourishment. The frequent patches of trees scattered throughout the savannah ( Joye, 2007) likely offered early hominids places to hide from predators and survey the plains in search of resources, mates, and prey (Appleton, 1975).…”
Section: Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…For pollinators and other wildlife, habitat is created in the city (Goddard et al, 2010). It has been suggested that UA can also alleviate poverty (van Veenhuizen & Danso, 2007;Zezza & Tasciotti, 2010), increase resiliency (to market fluctuations and climate change) (de Zeeuw et al, 2011), serve as a repository of agricultural knowledge (Koohafkan & Altieri, 2010) and an incubator of new technologies (Despommier, 2010), provide measurable improvements to human health and wellbeing (Joye, 2007;Ulrich, 2006), and reunite urbanites with natural systems from which they have been separated (McClintock, 2010;Turner, 2011). There is evidence that UA shifts dietary intake toward more fresh fruits and vegetables (McCormack et al, 2010), which may reduce emissions from fossil fuels (Weber & Matthews, 2008) and nitrogenous waste (Sutton et al, 2011), while contributing to human nutrition and reducing the risk of multiple chronic diseases (Boeing et al, 2012).…”
Section: Introductionmentioning
confidence: 99%